“The Journey in Tauris in 1820” by I. M. Muravyov-Apostol: Abstract and Concrete Reader in Author’s Compellation - A. A. Okhremenko (Научный диалог, 2017)
The article presents two views on the image of the addressee of the letters from “The Journey in Tauris” by I. M. Muravyov-Apostol. The study notes that the author of “The Journey...”, without specifying a particular person, creates an image of a reader poetically minded and interested in history, who tends to collect and analyze the information, knows (or at least interested in) ancient languages and culture, and dreams of his / her own journey in search of ancient artifacts. At the same time, having analyzed the text of the work and highlighted some facts from the author’s life, we see that the author’s compellation points to a concrete person - K. N. Batyushkov, friend and relative of the writer. In addition, these provisions help to recreate the image of the writer himself - scholar, great connoisseur of antiquity, rigorous researcher of antiquity, scientist seeking in his work to encompass all areas of knowledge; man who can impress the readers with his narrative. Given the fact that we have few memoirs of contemporaries about I. M. Muravyov-Apostol, this kind of material is of interest to create a literary portrait of the writer.